(untitled) (Journal of Comparative & International Higher Education, 2024)
This article examines how European regionalization influences Ukrainian public universities by exploring the Ukrainian education strategy and institutional internationalization and marketing policies. The study outlines specific historical and geopolitical conditions that have determined the development of the higher education system in Ukraine. Using a case study, the author analyses university development policies within regional, national, and local environments and examines challenges to and supports for the implementation of these policies. The analysis shows how the combined conflicting influences of the Bologna Process and Soviet legacies have affected Ukrainian universities. The article relies on the study results obtained before the Russian full-scale invasion of Ukraine. However, it also offers analysis of higher education internationalization reforms during the recent events of the Russia-Ukraine war.